ADAPTATION OF THE KNOWLEDGE MANAGEMENT SCALE TO TURKISH: A VALIDITY AND RELIABILITY STUDY (Third Sector Social Economic Review, 2023)
Purpose: This study aimed to examine the validity and reliability of the Knowledge Management Scale by adapting it to Turkish.Design/methodology/approach- Within the scope of the purpose of the research, the scale was applied to a total of 350 employees, the first sample of which was 132 and the second sample of which was 218 people.Cronbach Alpha internal consistency coefficient was calculated for the reliability of the scale. Confirmatory Factor Analysis was used to examine the construct validity of the scale. In order to reveal the criterion validity of the scale, the Knowledge Management Scale and the Learning Organization Scale were used, and it was determined that there were significant relationships between themFindings-  The findings confirm the five-factor structure of the scale as in the original. In the first sample of the study, Cronbach's Alpha coefficient varied between .747 and .897 in the sub-dimensions. In the second sample, Cronbach's Alpha coefficient varied between .827 and .908 in the sub-dimensions. The Cronbach's Alpha internal consistency coefficient of the scale in the total data was determined as .952.Discussion- The findings obtained as a result of the research show that the 24-item Knowledge Management Scale is valid and reliable. It is thought that the knowledge management scale can be used as a reliable and valid measurement tool in future studies and can meet the needs in measuring knowledge management in Turkey.
Keywords: Knowledge; Knowledge Management; Adapting Scale; Validity; Reliability